Progress and perspective of Li1 + xAlxTi2‐x(PO4)3 ceramic electrolyte in lithium batteries - Ke Yang (Wiley, 2021)
Abstract The replacement of liquid organic electrolytes with solid‐state electrolytes (SSEs) is a feasible way to solve the safety issues and improve the energy density of lithium batteries. Developing SSEs materials that can well match with high‐voltage cathodes and lithium metal anode is quite significant to develop high‐energy‐density lithium batteries. Li1 + xAlxTi2 ‐ x(PO4)3 (LATP) SSE with NASICON structure exhibits high ionic conductivity, low cost and superior air stability, which enable it as one of the most hopeful candidates for all‐solid‐state batteries (ASSBs). However, the high interfacial impedance between LATP and electrodes, and the severe interfacial side reactions with the lithium metal greatly limit its applications in ASSBs. This review introduces the crystal structure and ion transport mechanisms of LATP and summarizes the key factors affecting the ionic conductivity. The side reaction mechanisms of LATP with Li metal and the promising strategies for optimizing interfacial compatibility are reviewed. We also summarize the applications of LATP including as surface coatings of cathode particles, ion transport network additives and inorganic fillers of composite polymer electrolytes. At last, this review proposes the challenges and the future development directions of LATP in SSBs.